Interfacial electron transfer and bioelectrocatalysis of carbonized plant material as effective anode of microbial fuel cell. (1st March 2015) - Karthikeyan, Rengasamy; Wang, Bin; Xuan, Jin; Wong, Jonathan W.C.; Lee, Patrick K.H.; Leung, Michael K.H.
ABSTRACT: Effective use of natural materials to fabricate porous carbonaceous structures for anodes of microbial fuel cells (MFCs) has a high potential for substantial cost reduction in MFC. In this study, three kinds of plant materials, i.e. king mushroom, wild mushroom and corn stem, were investigated for fabrication of conductive electrode materials by simple carbonization procedures. Structure–reactivity relationships of these electrodes were systematically studied with electrochemical redox probe ([Fe(CN)6 ] 3−/4− ) and biofilm electroactivity. The electrochemical and bioelectrochemical accessibilities of the carbonized electrodes were evaluated by impedance, cyclic voltammetry and chronoamperometry techniques in order to study the electron transfer rate ( Kapp ), charge transfer resistances, oxidative current density and bioelectroactive moieties. The results showed that the electron transfer resistance ( Rct ) was 94 Ω for carbonized corn stem electrode with an electron transfer rate ( Kapp ) of 3.44 × 10 −2  cm s −1 for Fe 2+ /Fe 3+ redox probe. Higher bioelectroactivity (9.29 × 10 −8  mol cm −2 ) was found from biofilm on carbonized corn stem (Rbiofilm, 45 Ω) with an electron transfer rate (bacteria-anode) of 63 × 10 −5  cm s −1 . The maximum bioelectrocatalytic current ( imax ) of 3.12 mA cm −2 was obtained on carbon electrode derived from corn stem. That is 8 times higher than plain graphite electrode. The porous architecture, high electron transfer rate and high electroactive biofilm growth are attributes that qualify natural-material carbon anodes as low-cost alternative for MFC.